THEME: TOOLS FOR TEACHING FOREIGN LANGUAGES IN THE CONTINUOUS EDUCATION SYSTEM - Safarova Dildora; Abubakirova Zulayho; Makkashova Sohiba (Ustozlar uchun, 2025)
This article examines the various tools used for teaching foreign languages in the continuous education system, with a focus on modern technological advancements and traditional methods that continue to be effective. It explores the integration of digital learning platforms, mobile applications, language learning software, virtual reality (VR), augmented reality (AR), online collaborative environments, and conventional resources like textbooks and flashcards. The article highlights how these tools support personalized, flexible, and interactive learning experiences, allowing learners to acquire foreign language skills in a manner that suits their individual needs and preferences. The discussion underscores the importance of these tools in making language learning engaging, accessible, and relevant to modern learners in continuous education settings.